Closed-form solution for shock wave propagation in density-graded cellular material under impact. Issue 5 (July 2021) - Gupta, Vijendra; Kidane, Addis; Sutton, Michael
Highlights: Using shock front position as an independent variable fosters analytical solutions. Closed-form expressions derived for energy absorption capacity and incident stress. Density-graded structures have better energy absorption performance. Density gradation in cellular materials improves impact resistance. Faster and efficient design of density-graded structures for impact mitigation. Graphical abstract: Abstract: Density-graded cellular materials have tremendous potential in structural applications where impact resistance is required. Cellular materials subjected to high impact loading result in a compaction type deformation, usually modeled using continuum-based shock theory. The resulting governing differential equation of the shock model is nonlinear, and the density gradient further complicates the problem. Earlier studies have employed numerical methods to obtain the solution. In this study, an analytical closed-form solution is proposed to predict the response of density-graded cellular materials subjected to a rigid body impact. Solutions for the velocity of the impinging rigid body mass, energy absorption capacity of the cellular material, and the incident stress are obtained for a single shock propagation. The results obtained are in excellent agreement with the existing numerical solutions found in the literature. The proposed analytical solution can be potentially used for parametric studies and for effectively designing graded structures to mitigate impact.